2017
DOI: 10.3164/jcbn.16-86
|View full text |Cite
|
Sign up to set email alerts
|

Effects of patient age and choice of antisecretory agent on success of eradication therapy for <i>Helicobacter pylori</i> infection

Abstract: The effects of patient age on the efficacy of eradication treatment for Helicobacter pylori (H. pylori) remain unclear. The present study aimed to determine whether age affects eradication therapy involving vonoprazan, a novel potassium-competitive acid blocker (PCAB). We reviewed the cases of 3,261 patients who were administered first-line and second-line H. pylori eradication therapy at Toyoshima Endoscopy Clinic. The first-line treatment was clarithromycin and amoxicillin combined with a proton pump inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 19 publications
1
59
1
Order By: Relevance
“…Unlike the present study, recent Japanese retrospective studies of second-line H. pylori eradication therapy did not show a significant difference between PCAB and PPIbased regimens [21][22][23][24][25]. However, 4 studies showed a trend of superiority of PCAB over PPI-based regimens by 4-6% for second-line eradication success [21,22,24,25]. We can suggest 2 possible explanations why the past studies did not show statistically significant differences.…”
Section: Discussioncontrasting
confidence: 78%
“…Unlike the present study, recent Japanese retrospective studies of second-line H. pylori eradication therapy did not show a significant difference between PCAB and PPIbased regimens [21][22][23][24][25]. However, 4 studies showed a trend of superiority of PCAB over PPI-based regimens by 4-6% for second-line eradication success [21,22,24,25]. We can suggest 2 possible explanations why the past studies did not show statistically significant differences.…”
Section: Discussioncontrasting
confidence: 78%
“…A total of 133 studies were identified in the PubMed, EMBASE, and Cochrane Library databases. After reviewing the titles, abstracts, and full texts, we ultimately included 14 studies in the meta‐analysis. The detailed selection process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The detailed selection process is shown in Figure . In the 12 included studies, there are 2 well‐designed RCTs and 12 retrospective studies . The basic characteristics of all of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Treatment failure occurred more frequently in patients with 25‐OH vitamin D deficiency, whereas supplementing eradication therapy with vitamin C and E has no effect . A Japanese study found lower eradication rates with standard triple therapy in younger cohorts, perhaps reflecting poorer compliance …”
Section: Factors Of Treatment Failurementioning
confidence: 99%
“…80 A Japanese study found lower eradication rates with standard triple therapy in younger cohorts, perhaps reflecting poorer compliance. 81…”
Section: Fac Tor S Of Tre Atment Failurementioning
confidence: 99%